Another Bridge Across the Access to Justice Gap: LII's Virtual Reference Desk. Issue 2 (3rd April 2017) - Schneider, Charlotte D.
ABSTRACT: The Legal Information Institute (LII) has been at the forefront of access to justice for 25 years as the first organization to publish online the United States Code. More than just publishing the law online, the LII has been the leader in helping people find and understand the law since 1992, through innovative technologies they've created or employed for use with their collections and through partnerships with other like-minded organizations, groups, and individuals. Two decades later, the LII was inspired to help more people trying to find and understand the law. This summer will mark the third anniversary of the LII's virtual Reference Desk.